Cerebral venous thrombosis as presenting manifestation of inflammatory bowel disease (IBD). Issue 1 (29th January 2019) - Stamp, Katie; Pattinson, Alison; Maliakal, Paul; Nandakumar, Thekootu; Sebastian, Shaji
Abstract: Background: Venous thrombosis is an important complication in patients with inflammatory bowel disease (IBD) and has multifactorial origin mainly related to haemostatic changes in the presence of active inflammation. In addition, number of coagulation abnormalities may co‐exist in active IBD many of which return to normal once inflammatory process is controlled. Cerebral venous thrombosis (CVT) is a very rare but potentially serious extra‐intestinal feature in IBD Aim: To describe 2 cases of CVT associated with IBD and review the literature. Materials and methods: Records of 2 patients presenting to our unit with CVT and diagnosed to have IBD were reviewed. The clinical, laboratory, endoscopic and imaging data reviewed. We did a comprehensive literature Pubmed search using the search terms inflammatory bowel disease, colitis and venous thrombosis. Results: We report 2 cases with CVT from UC as a presenting manifestation. Both patients required biologics to control the severe colitis and one had some residual deficits in neurological function. In both patients, cerebral imaging improved on follow up Conclusions: Due to the rarity and variability in presentation, CVT as a presenting manifestation of IBD may be overlooked in emergency departments. Prompt diagnosis, initiation of anticoagulation and control of the pro‐coagulant state with treatment of colitis can lead to optimal recovery.